2021
DOI: 10.2967/jnmt.121.262440
|View full text |Cite
|
Sign up to set email alerts
|

Lung Perfusion Scintigraphy Early After COVID-19: A Single-Center Retrospective Study

Abstract: SD: conceived the study, interpretation of data, and writing the manuscript.MR, TL, RTG, DS: Data collection and interpretation of results. All authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Low-dose chest CT scans can be added to various perfusion SPECT investigations to reduce false-positive outcomes. Sajal et al ., Ozturk et al ., and Das et al [10,33,34] showed that adding a low-dose CT scan to a perfusion SPECT may exclude patients with structural anomalies more accurately diagnose pulmonary embolism. Overall, the bulk of included studies recommended adding SPECT/CT to planar perfusion/ventilation scans to decrease the possibility of false positive cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Low-dose chest CT scans can be added to various perfusion SPECT investigations to reduce false-positive outcomes. Sajal et al ., Ozturk et al ., and Das et al [10,33,34] showed that adding a low-dose CT scan to a perfusion SPECT may exclude patients with structural anomalies more accurately diagnose pulmonary embolism. Overall, the bulk of included studies recommended adding SPECT/CT to planar perfusion/ventilation scans to decrease the possibility of false positive cases.…”
Section: Discussionmentioning
confidence: 99%
“…Bahloul et al [16], two studies by Evbuomwan et al [24,25], Le Roux et al [29], Sajal et al [34], and Tan et al [37] reported pulmonary embolism prevalence by lung scintigraphy (VQ SPECT/CT). The prevalence ranged from 10.7% to 33.8%.…”
Section: Prevalence Of Pulmonary Embolism With Q or V/q Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported mismatched perfusion defects in early–post-COVID-19 patients, which may reflect a thromboembolic process ( Klok et al, 2020 ; Mueller-Peltzer et al, 2020 ; Roncon et al, 2020 ; Idilman et al, 2021 ; Mandal et al, 2021 ; Sajal et al, 2021 ). As hinted above, widespread microthrombi have been reported in multiple organ systems in patients with COVID-19.…”
Section: Pathobiology Of Pulmonary Vascular Diseases In Sars-cov-2mentioning
confidence: 99%